Valorization of Facts from animal wastes: Biodiesel production - Sampaio, Alberto (2011)
Two of the most important concerns regarding planet sustainability are energy management and waste disposal. Renewable energy sources and waste valorization processes are therefore very important. Among biofuels, biodiesel has very good utilization and environmental properties that allow partial or total replacement of diesel fuel. Biodiesel can be produced from residues like waste frying oils and animal fats. The purpose of this work is to produce biodiesel from fat obtained from industrial animal residues: green and lime fleshings from tanneries and slaughterhouses wastes. The fats were previously characterized and some of the samples presented a high acid value. For these materials, an acid esterification step prior to the transesterification reaction was needed, in order to lower the acid value. Transesterification with methanol was performed using sodium hydroxide or sodium methylate as catalysts, at 65ºC. The quality of biodiesel products was assessed by some of EN 14214 Standard parameters. The results show that most of the samples are within the specifications, except for high CFPP. This is typical of biodiesel produced from animal fats that present high saturated fatty acid content. Nevertheless, these products can be used in mixtures with biodiesel from vegetable oils, in order to meet standard specifications